Differential substitution: a contrastive hierarchy account - Archibald, John (Frontiers in Language Sciences, 2023)
In this paper I tackle the question of differential substitution in L2 phonology. A classic example of the phenomenon is learners from different L1s attempting to acquire the L2 English interdental fricative /θ/. Speakers of some languages (e.g., Japanese) tend to pronounce the /θ/ as [s] while speakers of other languages (e.g., Russian) tend to pronounce the /θ/ as [t]). Since both Japanese and Russian have both /s/ and /t/ in their phonemic inventories, it is interesting to ask why one language would choose [s] and the other [t]. What I argue in this paper is that it is not a local comparison of two sounds, or two features, or two phonemes that will determine why one segment rather than another is substituted. Rather, I argue that we must consider the formal representation of the entire segmental inventory (represented as a contrastive hierarchy) in order to understand why Japanese picks the [s] but Russian the [t] as the ‘best’ substitute for the English /θ/. What I will demonstrate is that in the languages that substitute [s], [continuant] is the highest- ranked feature which has scope over the place and voice features in the contrastive hierarchy of phonological features. In the languages that substitute [t], the place and voice features rank above [continuant].